Discriminative models, not discriminative training - Minka, Tom (2005)
The machine learning technique sometimes called "discriminative training" can be interpreted as ordinary training of a "discriminative model." This interpretation provides a better understanding of what discriminative training is really doing, and how it can be extended to partially-labeled data.